Can the modified ESG-KMV logit model explain the default risk of internet finance companies? - Zeng, Li; Lau, Wee-Yeap; Abdul Bahri, Elya Nabila (Frontiers in Environmental Science, 2022)
With the rapid development of internet finance in China, the risk management of internet finance has become an urgent issue. This study analyses the factors that affect the default risk of Chinese internet finance companies based on measuring the default distance of companies. This study incorporates ESG rating into the evaluation model to comprehensively reflect the default risk factors. The traditional KMV model is modified with ESG rating, and results are used to construct the panel logit model. Based on listed internet finance firms listed on China A-Shares data from 2016-2020, our results show: First, the modified ESG-KMV logit model can effectively analyze the influencing factors of internet finance default risk. Second, ROE accounts receivable turnover ratio, and asset-liability ratio z-value are important factors that affect the default risk of internet finance companies. Third, it is also found that COVID-19 has had a significant impact on the default risk of internet finance companies. As a policy implication, the regulator can incorporate ESG into the measurement of default risk to create more awareness among internet finance companies on the importance of the environment and sustainability to human societies.